Political Connection Heterogeneity and Green Technological Innovation: Evidence from Chinese Listed Companies - Siqi Meng; Xiaoyu Wu; Shuyang Wang (Systems)
With the continuous development of today’s economy and the growing interest in green technological innovation, this study investigates the impact of executive political connection heterogeneity (EPCH) on corporate green technological innovation (CGTI) in Chinese listed companies. Specifically, it distinguishes between ascribed and achieved political connections, examining their influence on incremental and radical CGTI. This study employs a quantitative research design, utilizing a sample of Chinese A-share listed companies from 2007 to 2022. Data are sourced from the China Securities Market & Accounting Research (CSMAR) database and the China National Research Data Service (CNRDS) database. The study analysis applies fixed-effect regression models to test the relationships between political connection heterogeneity and innovation outcomes. The findings reveal that ascribed political connections promote incremental innovation, while achieved political connections drive radical innovation. Moreover, strong GEO weakens the effect of ascribed political ties on incremental CGTI while enhancing the effect of achieved political ties on radical CGTI. These results contribute to the understanding of how political ties influence corporate innovation strategies and provide insights into the role of dynamic capabilities in green technological advancements.